Regulatory control of herbal and traditional medicines in Malaysia: issues and concerns - Ismail, Suzi Fadhilah; Abdul Ghani Azmi, Ida Madieha; Daud, Mahyuddin; Abd. Jalil, Juriah; Safuan, Sahida (Universiti Malaysia Sarawak, 2020)
Many herbs are believed to be beneficial in curing diseases, in addition to improving general health and wellbeing. With the booming of many herbal and traditional medicines into local markets, it is feared that the harmful side effects might prevail over their potential benefits as there is a lack of or even no scientific basis for the belief. The popularity of these medicines in the modern age is proliferated by the rapid growth of the internet usage worldwide vis-à-vis aggressive online marketing by the manufacturers, producers, retailers and sellers. These categories of medicines generally fall under the purview of various regulations such as the Control of Drugs and Cosmetics Regulations 1984, Sale of Drug Act 1952, Poison Act 1952, and the Advertisement and Sale Act 1956. Despite these regulations, production and sale of traditional medicines might pose some issues in relation to their safety to the consumers as they contain some new active ingredient of plant extracts which are chemicals that have the potential of causing adverse implication to health, similar to those purified medications. Generally, registration requirements for food supplements are not as stringent as those made applicable for pharmaceutical products and hence, many herbal and traditional medicines are registered under the former rather than the latter categories. Setting on this background, this paper seeks to examine the current legal framework regulating herbal and traditional medicines in Malaysia, with a special emphasis on the issues and challenges revolving around them. This paper uses qualitative research method, that is a content analysis of the existing literature from journals, articles, periodicals and various websites. Doctrinal analysis is applied to examine the relevant laws in selected jurisdictions, such as the United Kingdom, European Union, Australia and Japan, with the aim of emulating the most suitable, best practice from these countries. This paper concludes with some suggestions such as imposing the requirement of clinical evidence and adopting a systematic post-marketing surveillance to overcome the problems and weaknesses of the current legal mechanism in regulating products of herbal and traditional medicines.